2010
DOI: 10.1016/j.mce.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor in the rat epididymis: Expression, cellular distribution and regulation by steroid hormones

Abstract: Glucocorticoids regulate several physiological functions, including reproduction, in mammals. Curiously, little is known about glucocorticoid-induced effects on the epididymis, an androgen-dependent tissue with vital role on sperm maturation. Here, RT-PCR, Western blot and immunohistochemical studies were performed to evaluate expression, cellular distribution and hormonal regulation of glucocorticoid receptor (GR) along rat epididymis. The rat orthologue of human GRalpha (mRNA and protein) was detected in cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 89 publications
4
38
0
2
Order By: Relevance
“…Experimental conditions in which bilateral adrenalectomy was employed to manipulate the circulating levels of adrenal steroids further indicate an involvement of glucocorticoids in the modulation of spermatogenesis and testicular steroidogenesis (Lescoat et al, 1982;Saxena & Paul, 1987, 1988Gao et al, 1997;Weber et al, 2000), as well as in the fluid reabsorption by epithelial cells from the epididymis and vas deferens (Au et al, 1978;Turner & Cesarini, 1983;Phillips & Schultz, 2002). In agreement with these observations, the differential expression of the glucocorticoid receptor (GR) and 11b-hydroxysteroid dehydrogenase isoforms in tissues from the male reproductive tract of different species (Schultz et al, 1993;Mohler et al, 1996;Weber et al, 2000;Biagini & Pich, 2002;Waddell et al, 2003;Sharp et al, 2007;Silva et al, 2010;Gladstones et al, 2012;Cabrera-Sharp et al, 2013) indicate that they are targets for glucocorticoid actions. Previously, we showed that GR is constitutively expressed in the cytoplasm and nucleus of epididymal epithelial, interstitial and smooth muscle cells from the adult rat, suggesting that basal activation of GR by normal physiological levels of glucocorticoids occurs within the epididymis (Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Experimental conditions in which bilateral adrenalectomy was employed to manipulate the circulating levels of adrenal steroids further indicate an involvement of glucocorticoids in the modulation of spermatogenesis and testicular steroidogenesis (Lescoat et al, 1982;Saxena & Paul, 1987, 1988Gao et al, 1997;Weber et al, 2000), as well as in the fluid reabsorption by epithelial cells from the epididymis and vas deferens (Au et al, 1978;Turner & Cesarini, 1983;Phillips & Schultz, 2002). In agreement with these observations, the differential expression of the glucocorticoid receptor (GR) and 11b-hydroxysteroid dehydrogenase isoforms in tissues from the male reproductive tract of different species (Schultz et al, 1993;Mohler et al, 1996;Weber et al, 2000;Biagini & Pich, 2002;Waddell et al, 2003;Sharp et al, 2007;Silva et al, 2010;Gladstones et al, 2012;Cabrera-Sharp et al, 2013) indicate that they are targets for glucocorticoid actions. Previously, we showed that GR is constitutively expressed in the cytoplasm and nucleus of epididymal epithelial, interstitial and smooth muscle cells from the adult rat, suggesting that basal activation of GR by normal physiological levels of glucocorticoids occurs within the epididymis (Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…In agreement with these observations, the differential expression of the glucocorticoid receptor (GR) and 11b-hydroxysteroid dehydrogenase isoforms in tissues from the male reproductive tract of different species (Schultz et al, 1993;Mohler et al, 1996;Weber et al, 2000;Biagini & Pich, 2002;Waddell et al, 2003;Sharp et al, 2007;Silva et al, 2010;Gladstones et al, 2012;Cabrera-Sharp et al, 2013) indicate that they are targets for glucocorticoid actions. Previously, we showed that GR is constitutively expressed in the cytoplasm and nucleus of epididymal epithelial, interstitial and smooth muscle cells from the adult rat, suggesting that basal activation of GR by normal physiological levels of glucocorticoids occurs within the epididymis (Silva et al, 2010). We also demonstrated that the treatment with dexamethasone (DEX), a potent synthetic glucocorticoid highly selective for GR, induces GR activation in epididymal epithelial cells and changes in the gene expression in this organ in vivo, reinforcing the potential role of GR in epididymal biology (Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…A decrease in the level of testosterone affects conversion of round spermatids during spermiogenesis at stages 7 to 8 causing premature detachment that prevents elongation [O'Donnell et al 1996;Sofikitis et al 1999], thereby decreasing daily sperm production which may reflect our previous observation of decreased testosterone. Conversely, stress-induced corticosterone release might affect the epididymal microenvironment through the epithelial cytoplasmic and nuclear glucocorticoid receptor [Schultz et al 1993;Silva et al 2010]. The loss of total progressive motility could be owed to epididyimal corticosterone-induced ROS overproduction and lipid peroxidation [Dhanabalan et al 2010].…”
Section: Figure 8 Sperm Viability (A) Concentration (B) Total Spermentioning
confidence: 99%